Experimental study on continuous spill fire of liquid fuel on porous bed. Issue 1 (31st December 2023) - Zhai, Xu; Chen, Peng; Li, Liyang; Sun, Ruibang; Liu, Yang
ABSTRACT: As a traditional fossil fuel, petroleum fuel is prone to spills and fire accidents during storage, transportation, and use, which poses a great threat to the safe utilization of energy. This work aims to study the effect of porous media on the combustion characteristics of continuous spill fires. The transformer oil spill fire experiment is carried out on a porous bed with a length of 120 cm, a width of 15 cm, and a depth of 5 cm. The effects of sand diameter (0.75 mm, 1.5 mm, 3 mm, and 6 mm) and discharge rates (25 ml/min, 50 ml/min, and 75 ml/min) on the development of spill fires are analyzed. The results show that the spill fire fuel transport mechanism mainly includes gas phase diffusion caused by fuel consumption on the surface of a porous bed and liquid phase convection caused by capillary flow. Thus, three zones are formed from top to bottom: (i) the top vapor zone; (ii) the middle gas–liquid two-phase zone; and (iii) the bottom liquid phase zone. The presence of sand reduces the efficiency of the heat and mass. And it makes the spill fire stable combustion area increase compared with the smooth substrate. The stable combustion area has a positive correlation with the mass discharge rate and a negative correlation with the sand size. The stable combustion area of 1.5 mm, 3 mm, and 6 mm sand is 87.1%, 81.9%, and 77.5% of that of the 0.75 mm sand. In contrast to transformer oil pool fires and spill fires on smooth substrates, the burning rate is negatively related to the equivalent burning diameter. Meanwhile, the burning rate of spill fire on porous beds is significantly reduced compared with the first two. Based on the analysis of heat and mass transfer, a model for the burning rate of spill fire in porous media is formed and its correctness is verified. The experimental results are of great significance to the safe utilization of liquid energy.